Reconciliation. Imperative of the moment, biblical message and Christian task - González Faus, José Ignacio (Razón y fe, 2019)
Reconciliation is a word that, in principle, does not belong to religious language because it implies equality. With Paul this word becomes central in his message because with the incarnation there is a change in the ontological level of the human being. In spite of this, the word is said in the active sense only of God, and of man always in a passive voice. It expresses a full and definitive action of God, which must be activated in history. And it implies for the believer not only an announcement to proclaim but a service to be carried out: to rebuild full equality between God and men, which is impossible without full equality among all human beings.
Keywords: equality; God’s initiative; passivity; human activity